Application of composite hybrid based on oxygen-free photosynthetic bacteria in synchronous carbon sequestration and degradation of toxic refractory organic pollutants

By using complex hybrids based on non-oxygenated photosynthetic bacteria, including nano-ironite, nano-calcium carbonate and Pseudomonas marsh, the poor degradation effect and carbon emissions in wastewater were solved, and the effect of efficient degradation and carbon sequestration was achieved, and valuable resources were generated.

CN119750800AActive Publication Date: 2025-04-04GUANGDONG UNIV OF TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510109485.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-23
Publication Date
2025-04-04
Estimated Expiration
2045-01-23

AI Technical Summary

Technical Problem

The prior art is poor in degradation and easily lead to carbon emissions when purifying wastewater containing organic pollutants.

Method used

Complex hybrids based on non-oxygen-producing photosynthetic bacteria, including nano-ironite, nano-calcium carbonate and Pseudomonas marsh, are used to promote the multi-path degradation of organic pollutants such as antibiotics through photosynthetic heterotrophic and extracellular secretion of photosensitive active substances, while achieving the generation of carbon sequestration and valuable resources.

Benefits of technology

It significantly improves the degradation efficiency of organic pollutants, reduces carbon emissions, and generates valuable resources, solving the problems of poor degradation effects and carbon emissions in the prior art.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119750800A_ABST
    Figure CN119750800A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of water pollution treatment, and particularly relates to application of a composite hybrid based on oxygen-free photosynthetic bacteria in synchronous carbon sequestration and degradation of toxic refractory organic pollutants. The nano ferrihydrite, the nano calcium carbonate and the rhodopseudomonas palustris in the composite hybrid based on the oxygen-free photosynthetic bacteria provided by the invention can cooperate with one another, organic pollutants and fixed carbon are degraded through multiple ways, and valuable resources are generated; meanwhile, the nano ferrihydrite / nano calcium carbonate / rhodopseudomonas palustris / natural conductive high-molecular polymer hybrid can be loaded on the fiber brush by using the natural conductive high-molecular polymer, so that the rhodopseudomonas palustris rich in valuable resources such as protein and photosynthetic pigment is easier to recover; therefore, the technical problems that in the prior art, in the process of purifying the wastewater containing the organic pollutants, the effect of degrading toxic and refractory organic pollutants is poor, and carbon emission is large are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of water pollution treatment, and in particular to the application of a composite hybrid based on non-oxygen-producing photosynthetic bacteria in the simultaneous carbon fixation and degradation of toxic and difficult-to-degrade organic pollutants. Background Art

[0002] PPCPs include antibiotics, anti-inflammatory drugs, cosmetics, toiletries, etc. With the development of society, the types and usage of PPCPs have been increasing dramatically year by year. However, PPCPs have potential bioaccumulation and biotoxicity, especially antibiotics, which are prone to produce resistance genes. Antibiotics used as therapeutic drugs often enter the water system directly through feces, urine and other excreta without being completely metabolized, causing water pollution and seriously threatening human health and ecological safety.

[0003] At present, the main methods for purifying wastewater include physical treatment, chemical treatment and biological treatment. Physical treatment mainly removes suspended matter and some macromolecular organic matter through filtration, precipitation and adsorption, and is difficult to purify dissolved organic pollutants such as antibiotics. Chemical treatment mainly uses various chemical agents to react with pollutants to cause coagulation, precipitation, oxidation and reduction. However, the chemical agents used in chemical treatment are usually expensive and complicated to operate, and chemical agents are prone to secondary pollution. Biological treatment mainly treats pollutants that are easily degradable by themselves through activated sludge method, biofilm method and other methods, and has limited effect on organic pollutants such as antibiotics. In addition, in the process of biological treatment degrading organic pollutants, when organic carbon is degraded by microorganisms, the oxidation process will release a large amount of CO 2 Directly into the atmosphere, especially when treating wastewater containing high concentrations of organic matter, carbon emissions are more significant; at the same time, incomplete nitrification and denitrification reactions of microorganisms can easily lead to nitrous oxide (N 2 O) is emitted into the atmosphere. Nitrous oxide is a greenhouse gas that causes carbon emissions. By utilizing the ability of some microorganisms to assimilate and absorb carbon, nitrogen and other elements and convert them into biomass, it is possible to not only degrade carbon emissions but also recycle valuable resources.

[0004] There is an urgent need to develop and apply low-carbon or even zero-carbon water pollution treatment technologies to reduce direct or indirect greenhouse gas emissions and generate valuable resources, which have important application value. Summary of the invention

[0005] In view of this, the present application provides an application of a composite hybrid based on non-oxygen-producing photosynthetic bacteria in the simultaneous carbon fixation and degradation of toxic and difficult-to-degrade organic pollutants, which is used to solve the technical problems in the prior art of purifying wastewater containing organic pollutants, that is, the degradation of organic pollutants is not effective and carbon emissions are easily caused.

[0006] In a first aspect, the present application provides a composite hybrid based on non-oxygen-producing photosynthetic bacteria, comprising: nano-ferrihydrite, nano-calcium carbonate and Rhodopseudomonas palustris;

[0007] The nano calcium carbonate and Rhodopseudomonas palustris adhere to the surface of the nano ferrihydrite.

[0008] Preferably, the composite hybrid based on non-oxygen-producing photosynthetic bacteria further comprises: a natural conductive high molecular polymer;

[0009] The nano calcium carbonate and Rhodopseudomonas palustris are adhered to the surface of the nano ferrihydrite through a natural conductive high molecular polymer.

[0010] Preferably, the natural conductive high molecular polymer is a conductive alginate-based polymer.

[0011] Preferably, the mass ratio of sodium alginate to calcium sulfate in the raw materials used to form the conductive alginate-based polymer is 1:0.1-0.2.

[0012] Preferably, the particle size of the nano-ferrihydrite is 100-500 nm;

[0013] The particle size of the nano calcium carbonate is 20-100 nm.

[0014] Preferably, the particle size of the nano-ferrihydrite is 200-400 nm;

[0015] The particle size of the nano calcium carbonate is 30-50 nm.

[0016] The second aspect of the present application provides a method for preparing a composite hybrid based on non-oxygen-producing photosynthetic bacteria as described in the first aspect, the preparation method comprising the steps of:

[0017] Step A1, adding nano-ferrihydrite and nano-calcium carbonate to a suspension of Rhodopseudomonas palustris and stirring to obtain a preliminarily combined nano-ferrihydrite / nano-calcium carbonate / Rhodopseudomonas palustris hybrid suspension;

[0018] Step A2: co-cultivate the preliminarily combined nano-ferrihydrite / nano-calcium carbonate / Rhodopseudomonas palustris hybrid suspension under light, and separate the solid from the liquid to obtain the nano-ferrihydrite / nano-calcium carbonate / Rhodopseudomonas palustris hybrid.

[0019] Step A3: adding the nano-ferrihydrite / nano-calcium carbonate / Rhodopseudomonas palustris hybrid into a natural polymer salt solution, stirring the mixture sufficiently, and then performing ion cross-linking to obtain a composite hybrid based on non-oxygen-producing photosynthetic bacteria.

[0020] Preferably, in step A1, the concentration of the suspension of Rhodopseudomonas palustris is 9×108 ~ 3x10 9 cell L -1 .

[0021] Preferably, in step A1, the mass volume ratio of the nano-ferrihydrite, nano-calcium carbonate and Rhodopseudomonas palustris cell suspension is 0.2-0.8 g:0.2 g:1 L.

[0022] Preferably, in step A1, the stirring speed is 100-200 rpm and the time is 1-2 h.

[0023] Preferably, in step A2, the illumination intensity of the co-culture is 10000-60000 lx, the wavelength is 580-700 nm, and the time is 12-36 h.

[0024] Preferably, in step A2, the solid-liquid separation process is centrifugation at a speed of 5000 rpm for 30 minutes.

[0025] Preferably, in step A3, the mass volume ratio of the natural polymer salt solution is 1-3%.

[0026] The third aspect of the present application provides a composite hybrid carbon brush based on non-oxygen-producing photosynthetic bacteria, comprising: a fiber brush, a natural conductive polymer, and a composite hybrid based on non-oxygen-producing photosynthetic bacteria as described in the first aspect;

[0027] The composite hybrid based on non-oxygen-producing photosynthetic bacteria described in the first aspect is adhered and fixed to the bristle surface of the fiber brush through a conductive high molecular polymer hydrogel.

[0028] Preferably, the natural conductive high molecular polymer is a conductive alginate-based polymer.

[0029] The fourth aspect of the present application provides a method for preparing a composite hybrid carbon brush based on non-oxygen-producing photosynthetic bacteria as described in the third aspect, the preparation method comprising:

[0030] Step B1: Soak the conductive alginate-based polymer in 100 mM excess CaCl 2 solution for 1 day to obtain a rehydrated hydrogel;

[0031] Step B2, adding a composite hybrid based on non-oxygen-producing photosynthetic bacteria described in the first aspect or the second aspect to the rehydrated hydrogel to obtain a conductive polymer / hybrid mixed suspension;

[0032] Step B3: impregnate or spray the polymer / hybrid mixed suspension onto the bristle surface of the fiber brush, and solidify to obtain a composite hybrid carbon brush based on non-oxygen-producing photosynthetic bacteria.

[0033] The fifth aspect of the present application provides the use of a composite hybrid carbon brush based on non-oxygen-producing photosynthetic bacteria as described in the first aspect or a composite hybrid carbon brush based on non-oxygen-producing photosynthetic bacteria as described in the third aspect in simultaneous carbon fixation and degradation of toxic and difficult-to-degrade organic pollutants.

[0034] Preferably, the application of a composite hybrid based on non-oxygen-producing photosynthetic bacteria or a composite hybrid carbon brush based on non-oxygen-producing photosynthetic bacteria in the simultaneous carbon fixation and degradation of organic pollutants specifically includes: adding a composite hybrid based on non-oxygen-producing photosynthetic bacteria or a composite hybrid carbon brush based on non-oxygen-producing photosynthetic bacteria to wastewater containing sulfadiazine, and carrying out simultaneous carbon fixation and degradation of toxic and difficult-to-degrade organic pollutants under light.

[0035] Compared with the prior art, the application of a composite hybrid based on non-oxygen-producing photosynthetic bacteria in the simultaneous carbon fixation and degradation of toxic and difficult-to-degrade organic pollutants provided in the present application includes at least the following beneficial effects.

[0036] 1. In a composite hybrid based on non-oxygen-producing photosynthetic bacteria provided in the present application, nano-ferrihydrite can promote the photoheterotrophic metabolism of Rhodopseudomonas palustris, the extracellular secretion of photosensitizing active substances, the synthesis of adenosine triphosphate (ATP), and can also form a goethite conductive band. After the organic carbon source in the sewage is exhausted, nano-calcium carbonate can slowly release and dissolve bicarbonate under the action of Rhodopseudomonas palustris metabolism and acid production, which serves as the carbon source for the photosynthetic autotrophy of Rhodopseudomonas palustris, thereby realizing the Fe on the surface of ferrihydrite in the photosynthetic heterotrophic process of Rhodopseudomonas palustris to treat organic matter in sewage. 3+ Fe 2+ Reoxidized to Fe by photoautotrophic process 3+ , thus achieving the Fe 2+ / Fe 3+ Cycle and Fe 3+ Sustained-driven photosynthetic bioelectrochemical enhancement of carbon fixation and antibiotic degradation. This allows the nano-ferrihydrite / nano-calcium carbonate / Pseudomonas palustris / natural conductive polymer hybrid provided in this application to enhance the effect of degrading organic pollutants, fixing carbon and generating valuable resources through multiple pathways.

[0037] 2. In a composite hybrid based on non-oxygen-producing photosynthetic bacteria provided in the present application, the concentration of Rhodopseudomonas palustris, nano-ferrihydrite and nano-calcium carbonate during the preparation process is controlled to further enhance the effect of degrading organic pollutants, fixing carbon and generating valuable resources.

[0038] 3. The composite hybrid based on non-oxygen-producing photosynthetic bacteria provided in the present application can also form carbonization with a fiber brush, which is suitable for treating organic pollutants in wastewater with strong water flow and is easy to recover valuable resources. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] In order to more clearly illustrate the specific implementation methods of the present application or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0040] Figure 1 The scanning electron microscope image of the nano-ferrihydrite provided in Example 1 of the present application, the scanning electron microscope image of Rhodopseudomonas palustris, the scanning electron microscope image of the composite hybrid based on non-oxygen-producing photosynthetic bacteria, and the transmission electron microscope image of the composite hybrid based on non-oxygen-producing photosynthetic bacteria;

[0041] Figure 2 A schematic diagram of the removal rate and kinetics of sulfadiazine (SDZ) in simulated wastewater by a composite hybrid based on non-oxygenous photosynthetic bacteria, nano-ferrihydrite and Rhodopseudomonas palustris under light or dark conditions provided in Example 1 of the present application;

[0042] Figure 3 A schematic diagram of different degradation pathways of sulfadiazine (SDZ) in simulated wastewater by a composite hybrid based on non-oxygenous photosynthetic bacteria provided in Example 1 of the present application;

[0043] Figure 4 The present invention provides a composite hybrid based on non-oxygenous photosynthetic bacteria, nano-ferrihydrite and Rhodopseudomonas palustris at different concentrations provided in Examples 1-3 of the present invention, and the degradation of sulfadiazine (SDZ) in simulated wastewater under light or dark conditions in the process of CO 2 Schematic diagram of the generated quantities. DETAILED DESCRIPTION

[0044] The present application provides an application of a composite hybrid based on non-oxygen-producing photosynthetic bacteria in the simultaneous carbon fixation and degradation of toxic and difficult-to-degrade organic pollutants, which is used to solve the technical problems in the prior art of purifying wastewater containing organic pollutants, that is, the degradation of organic pollutants is not effective and carbon emissions are easily caused.

[0045] The technical solution of the present application will be described clearly and completely below in conjunction with the accompanying drawings. Obviously, the described embodiments are part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.

[0046] In view of the fact that in the process of purifying wastewater containing organic pollutants such as antibiotics by biological treatment and the like, on the one hand, the treatment effect of organic pollutants such as antibiotics is not good, and on the other hand, it is easy to cause carbon emission defects; the present application provides a composite hybrid based on non-oxygen-producing photosynthetic bacteria, namely, nano-ferrihydrite / nano-calcium carbonate / Pseudomonas palustris / natural polymer hybrid; the composition includes nano-ferrihydrite, nano-calcium carbonate and Pseudomonas palustris, and Pseudomonas palustris and nano-calcium carbonate are adhered to the surface of the nano-ferrihydrite.

[0047] In a composite hybrid based on non-oxygenous photosynthetic bacteria provided by the present application, polysaccharides, proteins and other extracellular polymers (EPS) secreted by Rhodopseudomonas palustris can make Rhodopseudomonas palustris adhere to the surface of nano-ferrihydrite and nano-calcium carbonate to form a nano-ferrihydrite / nano-calcium carbonate / Rhodopseudomonas palustris / natural conductive polymer hybrid; and after the formation of the nano-ferrihydrite / nano-calcium carbonate / Rhodopseudomonas palustris / natural conductive polymer hybrid, Rhodopseudomonas palustris can survive under light anaerobic or micro-aerobic conditions by using easily degradable organic matter in sewage as nutrients, and can also cooperate with nano-ferrihydrite to accelerate the degradation of organic pollutants such as antibiotics through multiple pathways, while enhancing the ability of Rhodopseudomonas palustris to fix carbon, reduce carbon emissions and generate valuable resources. Ferrihydrite nanoparticles can export photosynthetic electrons in Rhodopseudomonas palustris cells, stimulate Rhodopseudomonas palustris to secrete more degradation enzymes and photosensitive active substances, and promote the multi-pathway degradation of various toxic and difficult-to-degrade organic pollutants such as antibiotics in wastewater. Moreover, it produces more light-driven intracellular electron transfer accompanied by proton transfer, driving Rhodopseudomonas palustris to produce adenosine triphosphate (ATP) and reducing equivalents (NADPH), while also activating carbon fixation enzymes (such as RuBisCO) to enhance the CO produced during the fixation process. 2 , and convert it into valuable resource biomass, thereby achieving carbon fixation, reducing carbon emissions and generating valuable resources. Under photosynthetic heterotrophic conditions, Rhodopseudomonas palustris metabolizes the organic carbon source in the sewage and produces metabolic intermediates such as lactic acid, acetic acid and other organic acids. These acidic substances react chemically with nano-calcium carbonate to gradually release bicarbonate. When the organic carbon source in the sewage is exhausted, the released bicarbonate, as an important source of inorganic carbon fixation by bacteria, synthesizes three-carbon compounds (such as phosphoglyceraldehyde, PGA) through the Calvin cycle, and is further converted into cellular substances. Fe 2+ As an electron donor, it is reoxidized to Fe by photoautotrophic process 3+ , thus achieving the Fe 2+ / Fe 3+ cycle.

[0048] On the one hand, under illumination, Rhodopseudomonas palustris converts light energy into electrical energy through photoelectrochemical reactions, and then transfers electrons to the surface of ferrihydrite through its extracellular electron transfer. Nano-ferrihydrite, with its electron acceptor and electron transfer properties, helps bacteria to efficiently transfer electrons. This process significantly upregulates the expression of genes related to photosynthetic metabolic enzymes, extracellular electron transporters and extracellular degradation enzymes of Rhodopseudomonas palustris. This enhancement promotes the photoheterotrophic metabolism and extracellular secretion of photosensitizing active substances of Rhodopseudomonas palustris, thereby promoting the biodegradation and photosensitizing degradation of organic pollutants such as antibiotics. On the other hand, under illumination, Rhodopseudomonas palustris uses light energy to drive photosynthesis to produce reduced electrons and adenosine triphosphate (ATP). Nano-ferrihydrite participates in photoelectrochemical reactions as an electron acceptor, transferring the electrons produced by bacteria from outside the cell to the surface of ferrihydrite. Nano-ferrihydrite is accompanied by the transfer of protons during the electron reduction process. This synchronous transfer of protons and electrons is called proton coupling. The extracellular protons can be transferred to the bacterial cell membrane through the surface of ferrihydrite and enter the cell through the proton channel on the membrane. That is, in the process of electron transfer, ferrihydrite not only acts as an electron receptor, but also provides a proton transfer channel inside and outside the cell of Rhodopseudomonas palustris. The proton transfer forms a transmembrane proton gradient, which provides an additional driving force for Rhodopseudomonas palustris. This proton gradient provides additional energy for the adenosine triphosphate (ATP) synthase on the cell membrane to drive the synthesis of adenosine triphosphate (ATP). Through efficient adenosine triphosphate (ATP) synthesis and proton-coupled electron transfer, ferrihydrite helps bacteria improve the expression and activity of carbon fixation enzymes (such as RuBisCO), thereby accelerating the Calvin cycle and promoting the fixation of carbon dioxide. On the other hand, under light, Rhodopseudomonas palustris has the ability to photoheterotrophically reduce nano-ferrihydrite extracellularly, and forms a goethite conductive belt through direct contact. This conductive belt passes through the Fe 3+ , Fe 2+ Iron ions form a stable electron transfer channel, which enhances the efficiency of long-distance electron transfer, allowing bacteria to transfer electrons from the cell to the mineral surface and transfer them to other electron acceptors in the water over long distances, or directly participate in the reduction and degradation of pollutants. The released soluble Fe acts as an electron shuttle, which can transfer electrons between bacteria and pollutants, or directly undergo reduction reactions with pollutants in the water to promote their degradation. On the other hand, nano calcium carbonate has a large specific surface area, and its slow-release characteristics can maintain the inorganic carbon concentration in the water by gradually releasing bicarbonate, providing long-term and stable carbon source support for the photosynthetic autotrophy of bacteria, and ensuring the supply of inorganic carbon sources for photosynthetic autotrophy of Rhodopseudomonas palustris when the organic carbon source in the sewage is insufficient. The reduced Fe 2+ As an electron donor, it is reoxidized to Fe 3+The generated electrons drive the synthesis of ATP through the electron transport chain, providing energy for bacteria. They can also participate in the degradation of organic pollutants by generating free radicals or oxidized products. This dynamic balance mechanism meets the long-term metabolic needs of bacteria and forms an efficient and stable sewage purification and carbon emission reduction system. Therefore, the present application provides a composite hybrid based on non-oxygen-producing photosynthetic bacteria, in which Rhodopseudomonas palustris can also cooperate with nano-ferrihydrite, which can not only promote the photoheterotrophic metabolism of Rhodopseudomonas palustris and the extracellular secretion of photosensitizing active substances, enhance the degradation of organic pollutants such as antibiotics, but also promote the synthesis of adenosine triphosphate (ATP) and carbon-fixing enzymes (such as RuBisCO), enhance the Calvin cycle, and form a goethite conductive belt as a long-distance electron transmission channel for Rhodopseudomonas palustris, thereby enhancing the degradation of organic pollutants such as antibiotics. This makes the composite hybrid based on non-oxygen-producing photosynthetic bacteria provided by the present application not only efficient in degrading organic pollutants such as antibiotics, but also achieve carbon fixation, reduce carbon emissions and generate valuable resources, thereby overcoming the current process of purifying wastewater containing organic pollutants, the degradation of organic pollutants such as antibiotics is not effective, and it is easy to cause carbon emissions.

[0049] Preferably, in order to make nano-ferrihydrite have a higher surface area, stronger surface energy, and easier to adsorb and load Rhodopseudomonas palustris, the present application provides a composite hybrid based on non-oxygen-producing photosynthetic bacteria, in which the particle size of nano-ferrihydrite is controlled to be 100~500nm, the particle size of nano-calcium carbonate is 20~100nm, and the particle size of nano-calcium carbonate is smaller than that of nano-ferrihydrite. It is further preferred that the particle size of nano-ferrihydrite is 200~400nm, and the particle size of nano-calcium carbonate is 30~50nm.

[0050] At the same time, the composite hybrid based on non-oxygen-producing photosynthetic bacteria provided in the present application also introduces natural conductive high molecular polymers such as conductive alginate-based polymers, which on the one hand is beneficial to electron transmission and transfer, and on the other hand also improves the adhesion stability between nano-ferrihydrite, nano-calcium carbonate and Rhodopseudomonas palustris.

[0051] Correspondingly, the present application also provides a preparation method of a composite hybrid based on non-oxygen-producing photosynthetic bacteria, wherein the preparation method adds nano-ferrihydrite and nano-calcium carbonate to a suspension of Rhodopseudomonas palustris and stirs the suspension, and during the stirring process, Rhodopseudomonas palustris is fully contacted with nano-ferrihydrite and nano-calcium carbonate, so that it is adsorbed and loaded on the surface of nano-ferrihydrite and nano-calcium carbonate, and a preliminary combined nano-ferrihydrite / nano-calcium carbonate / Rhodopseudomonas palustris hybrid suspension is obtained; then co-culture is carried out under light, and during the co-culture process, the polysaccharides, proteins and other extracellular polymers (EPS) secreted by Rhodopseudomonas palustris can enhance the binding force between Rhodopseudomonas palustris and nano-ferrihydrite and nano-calcium carbonate, and Rhodopseudomonas palustris is adhered to the surface of nano-ferrihydrite, and then solid-liquid separation is performed to obtain a nano-ferrihydrite / nano-calcium carbonate / Rhodopseudomonas palustris hybrid. Subsequently, the hybrid is added to a natural polymer salt solution and stirred sufficiently, and a composite hybrid based on non-oxygen-producing photosynthetic bacteria is obtained by ionic crosslinking.

[0052] Preferably, in order to enable the palustrine Rhodopseudomonas to fully proliferate and perform photosynthesis to degrade organic pollutants, fix carbon and generate valuable resources; in the preparation method of a composite hybrid based on non-oxygen-producing photosynthetic bacteria provided in the present application, the amount of added nano-ferrihydrite and palustrine Rhodopseudomonas is also controlled, wherein the amount of palustrine Rhodopseudomonas in each liter of palustrine suspension is 9x10 8 ~3x10 9 cell, the amount of nano-ferrihydrite is 0.2~0.8g; while nano-calcium carbonate, as a reserve carbon source, does not directly participate in the synergistic effect of Rhodopseudomonas palustris and ferrihydrite. In order to ensure the stability and efficiency of the system, the amount of nano-calcium carbonate is controlled to be 0.2g; controlling the cell density of Rhodopseudomonas palustris can, on the one hand, improve the efficiency of degrading organic pollutants, fixing carbon and generating valuable resources, and on the other hand, avoid too much Rhodopseudomonas palustris which will make the competition for nutrients fierce, which is not conducive to the growth of bacteria and is easy to age; while controlling the concentration of nano-ferrihydrite can, on the one hand, improve the mutual synergistic effect with Rhodopseudomonas palustris, and on the other hand, avoid the excessive addition of nano-ferrihydrite blocking the light transmittance of the culture solution, thereby affecting the photosynthesis of bacteria and reducing the ability to remove pollutants.

[0053] Preferably, in order to enable Rhodopseudomonas palustris to secrete enough extracellular polymers (EPS) such as polysaccharides and proteins, they can be better adhered to the surface of nano-ferrihydrite, thereby photosynthesizing and degrading organic pollutants, fixing carbon and generating valuable resources; in a method for preparing a composite hybrid based on non-oxygen-producing photosynthetic bacteria provided in the present application, the light intensity of co-culture is also controlled to be 10000~60000lx, the wavelength is 580~700nm, and the time is 12~36h; the wavelength range of yellow light is between 580~590nm, and the wavelength range of white light is between 600~700nm. Within these wavelength and light intensity ranges, the pigment molecules of Rhodopseudomonas palustris can absorb light energy to the maximum extent and convert it into bioenergy.

[0054] Considering that the hybrid of nano-ferrihydrite / nano-calcium carbonate / Rhodopseudomonas palustris / natural high molecular polymer is a gel-like substance, it is easily dispersed and washed away in a water environment with strong water flow, which reduces the effect of degrading organic pollutants such as antibiotics and increases the difficulty of fixing carbon and recovering valuable resources; the present application also provides a composite hybrid carbon brush based on non-oxygen-producing photosynthetic bacteria; the composition includes a fiber brush, a natural conductive high molecular polymer and a hybrid of nano-ferrihydrite / nano-calcium carbonate / Rhodopseudomonas palustris / natural conductive high molecular polymer; the fiber brush is a current conventional fiber brush structure, including thousands of tiny bristles and a handle.

[0055] Accordingly, the present application also provides a method for preparing a composite hybrid carbon brush based on non-oxygen-producing photosynthetic bacteria. The preparation method comprises soaking the polymer in 100 mM excess CaCl 2 The mixture is placed in the solution for one day to obtain a rehydrated hydrogel, and nano-ferrihydrite / nano-calcium carbonate / Pseudomonas palustris / natural conductive polymer hybrid is added to obtain a conductive polymer / hybrid mixed suspension, which is then impregnated or sprayed onto the bristle surface of the fiber brush, and heated and cured to obtain a nano-ferrihydrite / nano-calcium carbonate / Pseudomonas palustris / natural conductive polymer hybrid carbon brush.

[0056] Correspondingly, the present application also provides an application of a composite hybrid based on non-oxygen-producing photosynthetic bacteria or a composite hybrid carbon brush based on non-oxygen-producing photosynthetic bacteria, and the specific application is: adding a composite hybrid based on non-oxygen-producing photosynthetic bacteria or a nano-ferrihydrite / nano-calcium carbonate / Pseudomonas palustris / natural polymer hybrid carbon brush to wastewater containing sulfadiazine, and simultaneously fixing carbon and degrading toxic and difficult-to-degrade organic pollutants under light.

[0057] The application of a composite hybrid based on non-oxygenous photosynthetic bacteria provided by the present application in simultaneous carbon fixation and degradation of toxic and difficult-to-degrade organic pollutants will be specifically described below in conjunction with embodiments and experimental examples.

[0058] Example 1

[0059] Example 1 of the present application provides a method for preparing a composite hybrid based on non-oxygen-producing photosynthetic bacteria, the preparation method comprising a step of preparing nano-ferrihydrite, a step of preparing nano-calcium carbonate, a step of culturing Rhodopseudomonas palustris, a step of adsorption and fixation, and a step of adhesion and fixation.

[0060] The preparation steps of nano ferrihydrite include:

[0061] Use ferrous sulfate ( ) or ferric chloride ( ) and other iron salts are dissolved in deionized water (25°C) to prepare an iron salt solution with a concentration of 0.5 mol / L; then 0.5 mol / L sodium hydroxide solution is slowly added dropwise to the iron salt solution and stirred to control the pH value at about 7-9 to form a reddish brown Fe(OH) 3 Then Fe(OH) 3 The precipitate was placed at room temperature for 6 hours or heated at 50-70°C for 2 hours, and the temperature and pH value were kept stable to allow Fe(OH) 3 Gradually transform into ferrihydrite precipitation, and promote the growth and structural stabilization of ferrihydrite crystals, to obtain ferrihydrite with good crystal structure and high specific surface area;

[0062] Separating the ferrihydrite precipitate from the supernatant using a centrifugal device or a filtering device, collecting the obtained ferrihydrite precipitate, and repeatedly washing the ferrihydrite precipitate with deionized water for 3-5 times to remove residual sulfate ions and unreacted sodium hydroxide to ensure the purity of the ferrihydrite;

[0063] The washed ferrihydrite precipitate is placed in a vacuum drying oven and dried at 60°C for 12 hours until the moisture is completely removed. The dried ferrihydrite is in a fine powder state. The particle size of the nano-ferrihydrite can be controlled within 100-300 nm through further grinding and screening to ensure its adsorption effect.

[0064] The preparation steps of nano calcium carbonate include:

[0065] Use sodium carbonate (Na 2 CO 3 ) and calcium chloride (CaCl 2 ) are dissolved in deionized water (25°C) to prepare a carbonate source solution and a calcium source solution with a concentration of 0.5 mol / L. Under mechanical or magnetic stirring conditions, the carbonate source solution is slowly added dropwise to the calcium source solution, and the dropping speed is kept uniform to prevent local oversaturation from causing particle agglomeration; the reaction temperature is controlled at 25–40°C, which is suitable for the formation of nanoparticles; the pH value of the system is maintained at 8.0–10.0 to ensure that calcium carbonate is generated in a stable form;

[0066] After the dropwise addition is completed, the reaction solution is continuously stirred for 30 minutes to 1 hour to allow the generated nano calcium carbonate particles to fully age, promote crystal growth and increase crystallinity; the precipitate is separated using a high-speed machine or a vacuum filter; the precipitate is repeatedly washed with deionized water until the conductivity of the washing liquid is close to the initial value of the deionized water, and unreacted ions and impurities are removed; the washed precipitate is dried at a low temperature of 50-80°C to prevent high temperature from causing crystal changes or agglomeration; the dried powder can be ground into a fine powder using a mortar or a ball mill;

[0067] By adjusting the concentration of calcium source and carbonate source, the addition speed, stirring speed and reaction temperature, the particle size of nano calcium carbonate (generally 20~60nm) can be effectively controlled; the use of stabilizers (such as PVP or citric acid) can reduce the agglomeration of nanoparticles during the generation and drying process.

[0068] The cultivation steps of Rhodopseudomonas palustris include:

[0069] Take the palustris Rhodopseudomonas and inoculate it into a sterilized liquid culture medium (including PBS, algae growth medium, trace metals, complex vitamins and carbon sources, etc.), and culture it anaerobically at 30°C, 10000~60000lx light, and a wavelength of 580~700nm for 5~7d to obtain the palustris Rhodopseudomonas seed solution; then inoculate the bacterial solution obtained from the primary culture into the liquid culture medium at a ratio of 1:100, and continue to culture it under light conditions for 48 hours to make the bacterial solution reach the logarithmic growth phase. The palustris Rhodopseudomonas has a higher activity and the ability to secrete extracellular polymers (EPS). The density of the palustris Rhodopseudomonas bacterial solution (OD600) is determined by a spectrophotometer. .

[0070] The adsorption and fixation steps include: adding an appropriate amount of nano-ferrihydrite according to a mass volume ratio of 0.5g:1L of the nano-ferrihydrite and the palustris red pseudomonas suspension, and then adding 0.2g of nano-calcium carbonate as a reserve carbon source, and using a magnetic stirrer to stir the mixed suspension at a speed of 100-200rpm for 1-2 hours, so that the contact between the nano-ferrihydrite particles, nano-calcium carbonate and the palustris red pseudomonas in the mixed suspension is more complete, and the palustris red pseudomonas and nano-calcium carbonate are adsorbed and fixed on the surface of the nano-ferrihydrite, so as to obtain a preliminarily combined nano-ferrihydrite / nano-calcium carbonate / Pseudomonas palustris hybrid suspension.

[0071] The adhesion and fixation steps include: continuing to co-culture the initially combined nano-ferrihydrite / nano-calcium carbonate / Rhodopseudomonas palustris hybrid suspension under the same lighting conditions. During the growth process, Rhodopseudomonas palustris will secrete extracellular polymers (EPS), such as polysaccharides and proteins. These substances not only help the bacteria to adhere, but also can further enhance the interaction between bacteria and ferrihydrite particles and nano-calcium carbonate. The adhesion effect of extracellular polymers (EPS) will further strengthen the combination between nano-ferrihydrite, nano-calcium carbonate and Rhodopseudomonas palustris, and enhance the stability of the nano-ferrihydrite / nano-calcium carbonate / Rhodopseudomonas palustris hybrid. The co-culture lasts for 24 hours to make the combination more stable.

[0072] After co-cultivation for 24 hours to complete adhesion and fixation, the nano-ferrihydrite, nano-calcium carbonate and Rhodopseudomonas palustris precipitates were separated by centrifugation at 5000 rpm for 30 minutes, and the precipitates were washed 2-3 times with deionized water to remove unadsorbed bacteria and other dissolved substances to ensure the purity and activity of nano-ferrihydrite, nano-calcium carbonate and Rhodopseudomonas palustris.

[0073] The steps for preparing the composite hybrid based on non-oxygenous photosynthetic bacteria include:

[0074] Sodium alginate is dissolved in water to form a uniform solution and then mixed with calcium sulfate (CaSO 4 ) slurry was mixed to prepare a polymer with a mass volume ratio of 2%, which is a conductive alginate-based polymer; nano-ferrihydrite / nano-calcium carbonate / Pseudomonas palustris hybrid was quickly added to form a composite hybrid based on non-oxygen-producing photosynthetic bacteria. The added CaSO 4 The mass of sodium alginate is 15% of that of sodium alginate to ensure that calcium ions are bound to the carboxyl groups of sodium alginate ( ) undergoes a preliminary cross-linking reaction to form a structurally stable ionic cross-linking system, providing a basis for subsequent processing.

[0075] Example 2

[0076] Example 2 of the present application provides a method for preparing a composite hybrid based on non-oxygen-producing photosynthetic bacteria, the preparation method comprising a step of preparing nano-ferrihydrite, a step of preparing nano-calcium carbonate, a step of culturing Rhodopseudomonas palustris, a step of adsorption and fixation, and a step of adhesion and fixation. The difference from Example 1 is that in the step of adsorption and fixation, the mass volume ratio of nano-ferrihydrite and Rhodopseudomonas palustris cell suspension is 0.2g:1L.

[0077] The preparation steps of nano ferrihydrite include:

[0078] Use ferrous sulfate ( ) or ferric chloride ( ) and other iron salts are dissolved in deionized water (25°C) to prepare an iron salt solution with a concentration of 0.5 mol / L; then 0.5 mol / L sodium hydroxide solution is slowly added dropwise to the iron salt solution and stirred to control the pH value at about 7-9 to form a reddish brown Fe(OH) 3 Precipitation, followed by Fe(OH) 3 The precipitate was placed at room temperature for 6 hours or heated at 50-70°C for 2 hours, and the temperature and pH value were kept stable to allow Fe(OH) 3 Gradually transform into ferrihydrite precipitation, and promote the growth and structural stabilization of ferrihydrite crystals, to obtain ferrihydrite with good crystal structure and high specific surface area;

[0079] Separating the ferrihydrite precipitate from the supernatant using a centrifugal device or a filtering device, collecting the obtained ferrihydrite precipitate, and repeatedly washing the ferrihydrite precipitate with deionized water for 3-5 times to remove residual sulfate ions and unreacted sodium hydroxide to ensure the purity of the ferrihydrite;

[0080] The washed ferrihydrite precipitate is placed in a vacuum drying oven and dried at 60°C for 12 hours until the water is completely removed. The dried ferrihydrite is in a fine powder state. The particle size of the nano ferrihydrite can be controlled to 100-300nm by further grinding and sieving to ensure its adsorption effect.

[0081] The preparation steps of nano calcium carbonate include:

[0082] Use sodium carbonate (Na 2 CO 3 ) and calcium chloride (CaCl 2 ) are dissolved in deionized water (25°C) to prepare a carbonate source solution and a calcium source solution with a concentration of 0.5 mol / L. Under mechanical or magnetic stirring conditions, the carbonate source solution is slowly added dropwise to the calcium source solution, and the dropping speed is kept uniform to prevent local oversaturation from causing particle agglomeration; the reaction temperature is controlled at 25–40°C, which is suitable for the formation of nanoparticles; the pH value of the system is maintained at 8.0–10.0 to ensure that calcium carbonate is generated in a stable form;

[0083] After the dropwise addition is completed, the reaction solution is continuously stirred for 30 minutes to 1 hour to allow the generated nano calcium carbonate particles to fully age, promote crystal growth and increase crystallinity; the precipitate is separated using a high-speed machine or a vacuum filter; the precipitate is repeatedly washed with deionized water until the conductivity of the washing liquid is close to the initial value of the deionized water, and unreacted ions and impurities are removed; the washed precipitate is dried at a low temperature of 50-80°C to prevent high temperature from causing crystal changes or agglomeration; the dried powder can be ground into a fine powder using a mortar or a ball mill;

[0084] By adjusting the concentration of calcium source and carbonate source, the addition speed, stirring speed and reaction temperature, the particle size of nano calcium carbonate (generally 20~60nm) can be effectively controlled; the use of stabilizers (such as PVP or citric acid) can reduce the agglomeration of nanoparticles during the generation and drying process.

[0085] The cultivation steps of Rhodopseudomonas palustris include:

[0086] Take the palustris Rhodopseudomonas and inoculate it into a sterilized liquid culture medium (including PBS, algae growth medium, trace metals, complex vitamins and carbon sources, etc.), and culture it anaerobically at 30°C, 10000~60000lx light, and a wavelength of 580~700nm for 5~7 days to obtain the palustris Rhodopseudomonas seed solution; then inoculate the bacterial solution obtained from the primary culture into the liquid culture medium at a ratio of 1:100, and continue to culture it under light conditions for 48 hours to make the bacterial solution reach the logarithmic growth phase. The palustris Rhodopseudomonas has a higher activity and the ability to secrete extracellular polymers (EPS). The density of the palustris Rhodopseudomonas bacterial solution (OD600) is about 1.08677 W / m2. .

[0087] The adsorption and fixation steps include: adding an appropriate amount of nano-ferrihydrite according to a mass volume ratio of 0.2g:1L of the nano-ferrihydrite and the palustris red pseudomonas cell suspension, and then adding 0.2g of nano-calcium carbonate as a reserve carbon source, and using a magnetic stirrer to stir the mixed suspension at a speed of 100-200rpm for 1-2 hours, so that the contact between the nano-ferrihydrite particles, nano-calcium carbonate and the palustris red pseudomonas in the mixed suspension is more complete, and the palustris red pseudomonas and nano-calcium carbonate are adsorbed and fixed on the surface of the nano-ferrihydrite, so as to obtain a preliminarily combined nano-ferrihydrite / nano-calcium carbonate / Pseudomonas palustris hybrid suspension.

[0088] The adhesion and fixation steps include: continuing to co-culture the initially combined nano-ferrihydrite / nano-calcium carbonate / Rhodopseudomonas palustris hybrid suspension under the same lighting conditions. During the growth process, Rhodopseudomonas palustris will secrete extracellular polymers (EPS), such as polysaccharides and proteins. These substances not only help the bacteria to adhere, but also can further enhance the interaction between bacteria and ferrihydrite particles and nano-calcium carbonate. The adhesion effect of extracellular polymers (EPS) will further strengthen the combination between nano-ferrihydrite, nano-calcium carbonate and Rhodopseudomonas palustris, and enhance the stability of the nano-ferrihydrite / nano-calcium carbonate / Rhodopseudomonas palustris hybrid. The co-culture lasts for 24 hours to make the combination more stable.

[0089] After co-cultivation for 24 hours to complete adhesion and fixation, the nano-ferrihydrite, nano-calcium carbonate and Rhodopseudomonas palustris precipitates were separated by centrifugation at 5000 rpm for 30 minutes, and the precipitates were washed 2-3 times with deionized water to remove unadsorbed bacteria and other dissolved substances to ensure the purity and activity of nano-ferrihydrite, nano-calcium carbonate and Rhodopseudomonas palustris.

[0090] The steps for preparing the composite hybrid based on non-oxygenous photosynthetic bacteria include:

[0091] Sodium alginate is dissolved in water to form a uniform solution and then mixed with calcium sulfate (CaSO 4 ) slurry was mixed to prepare a polymer with a mass volume ratio of 2%, which is a conductive alginate-based polymer; nano-ferrihydrite / nano-calcium carbonate / Pseudomonas palustris hybrid was quickly added to form a composite hybrid based on non-oxygen-producing photosynthetic bacteria. The added CaSO 4 The mass of sodium alginate is 15% of that of sodium alginate to ensure that calcium ions are bound to the carboxyl groups of sodium alginate ( ) undergoes a preliminary cross-linking reaction to form a structurally stable ionic cross-linking system, providing a basis for subsequent processing.

[0092] Example 3

[0093] Example 3 of the present application provides a method for preparing a composite hybrid based on non-oxygen-producing photosynthetic bacteria, the preparation method comprising a step of preparing nano-ferrihydrite, a step of preparing nano-calcium carbonate, a step of culturing Rhodopseudomonas palustris, a step of adsorption and fixation, and a step of adhesion and fixation. The difference from Example 1 is that in the step of adsorption and fixation, the mass volume ratio of nano-ferrihydrite and Rhodopseudomonas palustris cell suspension is 1g:1L.

[0094] The preparation steps of nano ferrihydrite include:

[0095] Use ferrous sulfate ( ) or ferric chloride ( ) and other iron salts are dissolved in deionized water (25°C) to prepare an iron salt solution with a concentration of 0.5 mol / L; then 0.5 mol / L sodium hydroxide solution is slowly added dropwise to the iron salt solution and stirred to control the pH value at about 7-9 to form a reddish brown Fe(OH) 3 Precipitation, followed by Fe(OH) 3 The precipitate was placed at room temperature for 6 hours or heated at 50-70°C for 2 hours, and the temperature and pH value were kept stable to allow Fe(OH) 3 Gradually transform into ferrihydrite precipitation, and promote the growth and structural stabilization of ferrihydrite crystals, to obtain ferrihydrite with good crystal structure and high specific surface area;

[0096] Separating the ferrihydrite precipitate from the supernatant using a centrifugal device or a filtering device, collecting the obtained ferrihydrite precipitate, and repeatedly washing the ferrihydrite precipitate with deionized water for 3-5 times to remove residual sulfate ions and unreacted sodium hydroxide to ensure the purity of the ferrihydrite;

[0097] The washed ferrihydrite precipitate is placed in a vacuum drying oven and dried at 60°C for 12 hours until the water is completely removed. The dried ferrihydrite is in a fine powder state. The particle size of the nano ferrihydrite can be controlled to 100-300nm by further grinding and sieving to ensure its adsorption effect.

[0098] The preparation steps of nano calcium carbonate include:

[0099] Use sodium carbonate (Na 2 CO 3 ) and calcium chloride (CaCl 2 ) are dissolved in deionized water (25°C) to prepare a carbonate source solution and a calcium source solution with a concentration of 0.5 mol / L. Under mechanical or magnetic stirring conditions, the carbonate source solution is slowly added dropwise to the calcium source solution, and the dropping speed is kept uniform to prevent local oversaturation from causing particle agglomeration; the reaction temperature is controlled at 25–40°C, which is suitable for the formation of nanoparticles; the pH value of the system is maintained at 8.0–10.0 to ensure that calcium carbonate is generated in a stable form;

[0100] After the dropwise addition is completed, the reaction solution is continuously stirred for 30 minutes to 1 hour to allow the generated nano calcium carbonate particles to fully age, promote crystal growth and increase crystallinity; the precipitate is separated using a high-speed machine or a vacuum filter; the precipitate is repeatedly washed with deionized water until the conductivity of the washing liquid is close to the initial value of the deionized water, and unreacted ions and impurities are removed; the washed precipitate is dried at a low temperature of 50-80°C to prevent high temperature from causing crystal changes or agglomeration; the dried powder can be ground into a fine powder using a mortar or a ball mill;

[0101] By adjusting the concentration of calcium source and carbonate source, the addition speed, stirring speed and reaction temperature, the particle size of nano calcium carbonate (generally 20~60nm) can be effectively controlled; the use of stabilizers (such as PVP or citric acid) can reduce the agglomeration of nanoparticles during the generation and drying process.

[0102] The cultivation steps of Rhodopseudomonas palustris include:

[0103] Take the palustris Rhodopseudomonas and inoculate it into a sterilized liquid culture medium (including PBS, algae growth medium, trace metals, complex vitamins and carbon sources, etc.), and culture it anaerobically at 30°C, pH=6.5~7.5, 10000~60000lx light, and a wavelength of 580~700nm for 5~7 days to obtain the palustris Rhodopseudomonas seed solution; then inoculate the bacterial solution obtained from the primary culture into the liquid culture medium at a ratio of 1:100, and continue to culture it under suitable temperature, pH and light conditions for 48 hours to make the bacterial solution reach the logarithmic growth phase. The palustris Rhodopseudomonas has a higher activity and the ability to secrete extracellular polymers (EPS). The density (OD600) of the palustris Rhodopseudomonas bacterial solution is determined by a spectrophotometer. .

[0104] The adsorption and fixation steps include: adding an appropriate amount of nano-ferrihydrite according to the mass volume ratio of nano-ferrihydrite to the palustris red pseudomonas cell suspension of 1g:1L, adding 0.2g of nano-calcium carbonate as a reserve carbon source, and stirring the mixed suspension with a magnetic stirrer at a speed of 100-200rpm for 1-2 hours, so that the contact between the nano-ferrihydrite particles, nano-calcium carbonate and the palustris red pseudomonas in the mixed suspension is more complete, and the palustris red pseudomonas and nano-calcium carbonate are adsorbed and fixed on the surface of the nano-ferrihydrite, so as to obtain a preliminarily combined nano-ferrihydrite / nano-calcium carbonate / Pseudomonas palustris hybrid suspension.

[0105] The adhesion and fixation steps include: continuing to co-culture the initially combined nano-ferrihydrite / nano-calcium carbonate / Rhodopseudomonas palustris hybrid suspension under the same lighting conditions. During the growth process, Rhodopseudomonas palustris will secrete extracellular polymers (EPS), such as polysaccharides and proteins. These substances not only help the bacteria to adhere, but also can further enhance the interaction between bacteria and ferrihydrite particles and nano-calcium carbonate. The adhesion effect of extracellular polymers (EPS) will further strengthen the combination between nano-ferrihydrite, nano-calcium carbonate and Rhodopseudomonas palustris, and enhance the stability of the nano-ferrihydrite / nano-calcium carbonate / Rhodopseudomonas palustris hybrid. The co-culture lasts for 24 hours to make the combination more stable.

[0106] After co-cultivation for 24 hours to complete adhesion and fixation, the nano-ferrihydrite, nano-calcium carbonate and Rhodopseudomonas palustris precipitates were separated by centrifugation at 5000 rpm for 30 minutes, and the precipitates were washed 2-3 times with deionized water to remove unadsorbed bacteria and other dissolved substances to ensure the purity and activity of nano-ferrihydrite, nano-calcium carbonate and Rhodopseudomonas palustris.

[0107] The steps for preparing the composite hybrid based on non-oxygenous photosynthetic bacteria include:

[0108] Sodium alginate is dissolved in water to form a uniform solution and then mixed with calcium sulfate (CaSO 4 ) slurry was mixed to prepare a polymer with a mass volume ratio of 2%, which is a conductive alginate-based polymer; nano-ferrihydrite / nano-calcium carbonate / Pseudomonas palustris hybrid was quickly added to form a composite hybrid based on non-oxygen-producing photosynthetic bacteria. The added CaSO 4 The mass of sodium alginate is 15% of that of sodium alginate to ensure that calcium ions are bound to the carboxyl groups of sodium alginate ( ) undergoes a preliminary cross-linking reaction to form a structurally stable ionic cross-linking system, providing a basis for subsequent processing.

[0109] Example 4

[0110] Example 4 of the present application provides a method for preparing a composite hybrid carbon brush based on non-oxygen-producing photosynthetic bacteria, the preparation method comprising the steps of preparing a conductive polymer / hybrid mixed suspension and loading it onto a fiber brush.

[0111] The steps of preparing the conductive polymer / hybrid mixed suspension include: dissolving sodium alginate in water and mixing with calcium sulfate (CaSO 4 ) slurry was mixed to prepare a polymer with a mass volume ratio of 2%. The added CaSO 4 The mass of the pregel was 15% of the mass of sodium alginate. The polymer was immediately molded and gelled between glass plates using a 3 mm thick spacer and then stored in a cooler at 5°C for 1 day to complete the ionic crosslinking. The prepared pregel was anisotropically dried / shrunk in a flat bottom dish at 20–25°C and 20–25% relative humidity (RH) for 3 days. The obtained dry sheets were soaked in 100 mM excess CaCl 2 The solution was kept for 1 day to improve the conductivity and mechanical properties of the material through deep crosslinking of multivalent metal ions, and the rehydrated hydrogel was obtained after washing with distilled water. Then, a composite hybrid based on non-oxygenous photosynthetic bacteria prepared in any one of Examples 1-3 was mixed with the rehydrated hydrogel at a ratio of 30% (w / v), and stirred evenly to form a conductive polymer / hybrid mixed suspension.

[0112] The step of loading onto the fiber brush includes: immersing the treated bristles of the fiber brush into a conductive polymer / hybrid mixed suspension, stirring continuously at a speed of 100-150 rpm for 2-4 hours to allow the bristles to be fully immersed, or spraying the conductive polymer / hybrid mixed suspension onto the bristles of the fiber brush, and then placing it at room temperature or heating to cure to obtain a composite hybrid carbon brush based on non-oxygen-producing photosynthetic bacteria.

[0113] According to the water flow rate and pollutant concentration, the prepared composite hybrid carbon brush based on non-oxygen-producing photosynthetic bacteria is evenly distributed and installed on a fixed frame in the biological treatment tank or suspended above the water body to degrade organic pollutants, fix carbon and generate valuable resources. At the same time, since the nano-ferrihydrite / Pseudomonas palustris hybrid is loaded on the fiber brush, it is very easy to recover the valuable resources.

[0114] Experimental Example 1

[0115] This Experimental Example 1 performs microstructural characterization on the nano-ferrihydrite, Rhodopseudomonas palustris and the composite hybrid based on non-oxygen-producing photosynthetic bacteria provided in Example 1.

[0116] Among them, the scanning electron microscope image of nano-ferrihydrite is as follows Figure 1 As shown in Figure a, the scanning electron microscope image of Rhodopseudomonas palustris is as follows Figure 1 As shown in Figure b, it can be seen that nano-ferrihydrite aggregates together to form irregular agglomerates with a loose and porous surface, which is conducive to the adsorption load of Rhodopseudomonas palustris, while the surface of Rhodopseudomonas palustris is smooth.

[0117] The morphology of Rhodopseudomonas palustris and nano-calcium carbonate after being fixed to nano-ferrihydrite is as follows: Figure 1 As shown in Figure c, from Figure 1 From the scanning electron microscopy image of the composite hybrid based on non-oxygen-producing photosynthetic bacteria shown in Figure c, it can be seen that Rhodopseudomonas palustris and nano-calcium carbonate are tightly attached to the surface of nano-ferrihydrite, indicating that nano-ferrihydrite can provide abundant attachment sites for Rhodopseudomonas palustris and nano-calcium carbonate. Nano-calcium carbonate serves as a supplementary carbon source, and the direct contact between Rhodopseudomonas palustris and nano-ferrihydrite is beneficial to the degradation of organic pollutants, carbon fixation and the generation of valuable resources. The interaction mode between Rhodopseudomonas palustris and nano-ferrihydrite is shown in the transmission electron microscopy image shown in Figure 1d. Rhodopseudomonas palustris directly transfers electrons by contacting the surface of nano-ferrihydrite. Nano-ferrihydrite serves as a terminal electron acceptor, and partial mineral dissolution of ferrihydrite occurs. The ferrihydrite is dissolved to form a conductive belt, and the released soluble iron acts as an electron shuttle to promote long-distance electron transfer. In addition, some dissolved nano-ferrihydrite enters the cell through the cell membrane and undergoes alienation reduction in the cell, or ferrihydrite, as an electron conductor, is embedded in the cell membrane, thereby promoting the transfer of electrons from the inside to the outside of the cell, and enhancing the energy acquisition and electron transfer efficiency of Rhodopseudomonas palustris through multiple pathways, thereby accelerating the degradation of organic pollutants such as antibiotics. At the same time, the ferrihydrite crystal phase structure is changed, and it acts as an electron transfer medium in a cycle, which significantly improves the carbon fixation ability of the bacteria. At the same time, Rhodopseudomonas palustris is rich in valuable resources such as protein, thereby achieving the degradation of organic pollutants, fixing carbon and generating valuable resources.

[0118] Experimental Example 2

[0119] In this Experimental Example 2, the nano-ferrihydrite, Rhodopseudomonas palustris and the composite hybrid based on non-oxygen-producing photosynthetic bacteria provided in Examples 1-3 were used to test the performance of degrading the organic pollutant sulfadiazine (SDZ).

[0120] Performance testing includes the following steps:

[0121] The steps for preparing simulated wastewater are as follows: PBS, algae media, trace metals, vitamins, anhydrous sodium acetate, sulfadiazine and other ingredients are added into deionized water to prepare simulated wastewater, and the concentration of sulfadiazine (SDZ) in the simulated wastewater is controlled to be 1 mg / L.

[0122] The removal rate and kinetic test steps of sulfadiazine (SDZ) in simulated wastewater were as follows: the nano-ferrihydrite (0.5 g: 1 L) provided in Example 1 and Rhodopseudomonas palustris ( ) and a composite hybrid based on anoxygenic photosynthetic bacteria (the mass volume ratio of nanoferrihydrite and Rhodopseudomonas palustris suspension was 0.5 g:1 L) were added to simulated wastewater at the same concentration, and then the degradation of sulfadiazine (SDZ) was observed within 96 h under light or dark conditions; among them, three parallel groups were set up during the test to reduce experimental errors, and the concentration of sulfadiazine (SDZ) was tested every 12 h. The concentration of sulfadiazine (SDZ) was determined by high performance liquid chromatography (HPLC, Essentia LC-16; Shimadzu Corporation, Japan) at a wavelength of 265 nm. The mobile phase consisted of 90:10 (v:v) 0.1% formic acid and acetonitrile, and the removal rate of sulfadiazine (SDZ) was calculated by the formula C 0 -C t / C 0 To calculate, where C 0 -C t is the concentration of sulfadiazine (SDZ) at 12-hour intervals. Figure 2 As shown in Figure 2, the results of different degradation and removal pathways of sulfadiazine (SDZ) in simulated wastewater by nanoferrihydrite-Pseudomonas palustris hybrid are shown in Figure 2. Figure 3 shown.

[0123] CO degradation during sulfadiazine (SDZ) degradation in simulated wastewater 2 The generation test steps were as follows: CO in the headspace was measured by gas chromatography (FULI GC9790II, China). 2 The test lasted for 8 days; the gas chromatography used the following parameters: separation column TDX-01 ( ); carrier gas argon, 45mL / min; column temperature, 120℃; detector temperature: 160℃; injection temperature 160℃, the results are as follows Figure 4 shown.

[0124] from Figure 2 It can be seen that the effect of Rhodopseudomonas palustris on the degradation and removal of sulfadiazine (SDZ) is poor under light. After 96 hours, the degradation and removal rate of sulfadiazine (SDZ) is only 43.3%, while the degradation and removal rate of sulfadiazine (SDZ) by the composite hybrid based on non-oxygen-producing photosynthetic bacteria provided in Example 1 can reach 83.3%. Under the same added concentration, the degradation and removal rate of sulfadiazine (SDZ) by the nano-ferrihydrite / Rhodopseudomonas palustris hybrid is greater than the sum of the degradation and removal rates of sulfadiazine (SDZ) by Rhodopseudomonas palustris and nano-ferrihydrite; at the same time, the first-order kinetic curve of sulfadiazine (SDZ) shows that under light, the degradation and removal rate of sulfadiazine (SDZ) by Rhodopseudomonas palustris is only 43.3%, respectively. Compared with the degradation rate constant k of , the SDZ degradation rate constant k of the composite hybrid based on anoxygenic photosynthetic bacteria can reach , which was increased by 3.24 times; at the same time, under dark conditions, the SDZ removal rate of the composite hybrid based on anoxygenic photosynthetic bacteria was only 7.9%, and the degradation rate constant k was , indicating that the hydrolysis of the composite hybrid based on anoxygenic photosynthetic bacteria has little effect on it in the process of treating wastewater. , However, nano-ferrihydrite can hardly degrade and remove sulfadiazine (SDZ) under light.

[0125] from Figure 3 It can be seen that the composite hybrid based on anoxygenic photosynthetic bacteria can degrade and metabolize sulfadiazine (SDZ) through multiple pathways. The composite hybrid based on anoxygenic photosynthetic bacteria can remove sulfadiazine (SDZ) through multiple pathways such as direct enzymatic biodegradation, EPS-mediated indirect photodegradation and adsorption; in the first 24 hours, biodegradation was the main removal mechanism, contributing 25%, which may be because the dissolved nano-ferrihydrite entered the interior of the Rhodopseudomonas palustris cells, where different reductions occurred to produce energy, enhancing cellular metabolism. In addition, it also served as an iron source for the synthesis of cell components, thereby promoting the growth of Rhodopseudomonas palustris; after 24 hours, the indirect photodegradation ability increased. The contribution of nano-ferrihydrite to the adsorption of sulfadiazine (SDZ) increased with time, which may be due to the extracellular reduction of ferrihydrite stimulating purple non-sulfur photosynthetic bacteria to secrete extracellular polymers (EPS), or the transformation of ferrihydrite crystal phase to form a conductive pathway, leading to enhanced adsorption.

[0126] from Figure 4It can be seen that the composite hybrid based on anoxygenic photosynthetic bacteria provided in Examples 1-3, the nano-ferrihydrite provided in Example 1, and Rhodopseudomonas palustris have carbon fixation effects under light or dark conditions; Figure 4 It can be seen that as time goes by, almost no carbon dioxide is produced in the nanoferrihydrite system under light, while the total amount of carbon dioxide released by Rhodopseudomonas palustris and the composite hybrid based on non-oxygen-producing photosynthetic bacteria increases accordingly, reaching the highest value on the eighth day. This is because in the process of metabolizing organic matter, Rhodopseudomonas palustris decomposes complex organic compounds through a series of biochemical reactions to generate the final product carbon dioxide, while providing energy for cells to maintain growth and physiological functions. Although Rhodopseudomonas palustris can decompose organic matter to produce carbon dioxide, it also has the ability of photosynthesis and can use light energy to fix carbon dioxide in the environment into organic matter through the Calvin cycle. Therefore, bacteria reach a dynamic balance between carbon fixation and carbon release: decomposing organic matter to release carbon dioxide, and at the same time re-fixing part of the carbon dioxide into organic matter through the Calvin cycle under photosynthetic conditions. Further comparison shows that as time goes on, the rate of carbon dioxide released by Rhodopseudomonas palustris under light is the fastest, and the total amount of carbon dioxide released is also the largest, while the rate and total amount of carbon dioxide released by the composite hybrid based on non-oxygen photosynthetic bacteria provided in Example 2 (0.2g / L nano-ferrihydrite), the composite hybrid based on non-oxygen photosynthetic bacteria provided in Example 3 (1g / L nano-ferrihydrite), and the hybrid of nano-ferrihydrite / Rhodopseudomonas palustris under dark conditions (1g / L nano-ferrihydrite) gradually decrease, and in the dark environment, the activity of Rhodopseudomonas palustris is significantly reduced, and the growth rate of carbon dioxide content slows down, indicating that light is crucial to the growth process of bacteria. Nano-ferrihydrite without the addition of Rhodopseudomonas palustris has almost no significant increase in carbon dioxide content, and the carbon dioxide content is basically maintained at the initial level, indicating that nano-ferrihydrite itself does not have the ability to fix carbon and needs to work synergistically with bacteria. The rate and total amount of carbon dioxide released by the composite hybrid based on non-oxygen-producing photosynthetic bacteria (0.5 g / L nano-ferrihydrite) provided in Example 1 under illumination are close to the rate and total amount of carbon dioxide released by the composite hybrid based on non-oxygen-producing photosynthetic bacteria (1 g / L nano-ferrihydrite) provided in Example 3 under illumination, which indicates that when the concentration of nano-ferrihydrite increases to 0.5 g / L nano-ferrihydrite, it has achieved a good synergistic effect with Rhodopseudomonas palustris, and has exerted a good effect of degrading organic pollutants, fixing carbon and generating valuable resources.

[0127] The above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them. Although the present application has been described in detail with reference to the aforementioned embodiments, a person skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some or all of the technical features thereof may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the scope of the technical solutions of the embodiments of the present application.

Claims

1. A composite hybrid based on non-oxygen-producing photosynthetic bacteria, characterized in that: include: Nanoferrihydrite, nanocalcium carbonate, and Rhodopseudomonas palustris; The nano calcium carbonate and Rhodopseudomonas palustris adhere to the surface of the nano ferrihydrite.

2. A composite hybrid based on non-oxygen-producing photosynthetic bacteria according to claim 1, characterized in that: The composite hybrid based on non-oxygen-producing photosynthetic bacteria further comprises: a natural conductive high molecular polymer; The nano calcium carbonate and Rhodopseudomonas palustris are adhered to the surface of the nano ferrihydrite through a natural conductive high molecular polymer.

3. A composite hybrid based on non-oxygen-producing photosynthetic bacteria according to claim 2, characterized in that: The natural conductive high molecular polymer is a conductive alginate-based polymer.

4. A composite hybrid based on non-oxygen-producing photosynthetic bacteria according to claim 1, characterized in that: The particle size of the nano ferrihydrite is 100-500 nm, the particle size of the nano calcium carbonate is 20-100 nm, and the particle size of the nano calcium carbonate is smaller than that of the nano ferrihydrite.

5. A method for preparing a composite hybrid based on non-oxygen-producing photosynthetic bacteria according to any one of claims 1 to 4, characterized in that: Includes steps: Step A1, adding nano-ferrihydrite and nano-calcium carbonate to a suspension of Rhodopseudomonas palustris and stirring to obtain a preliminarily combined nano-ferrihydrite / nano-calcium carbonate / Rhodopseudomonas palustris hybrid suspension; Step A2, co-culturing the preliminarily combined nano-ferrihydrite / nano-calcium carbonate / Rhodopseudomonas palustris hybrid suspension under light, and performing solid-liquid separation to obtain nano-ferrihydrite / nano-calcium carbonate / Rhodopseudomonas palustris hybrid; Step A3: adding the nano-ferrihydrite / nano-calcium carbonate / Rhodopseudomonas palustris hybrid into a natural polymer salt solution, stirring the mixture sufficiently, and then performing ion cross-linking to obtain a composite hybrid based on non-oxygen-producing photosynthetic bacteria.

6. The method for preparing a composite hybrid based on non-oxygen-producing photosynthetic bacteria according to claim 5, characterized in that: In step A1, the concentration of the Rhodopseudomonas palustris cell suspension is The mass volume ratio of the nano-ferrihydrite, nano-calcium carbonate and Rhodopseudomonas palustris suspension is 0.2~:1g:0.2g:1L; In step A2, the co-culture light intensity is 10000-60000 lx, the wavelength is 580-700 nm, and the time is 12-36 h; In step A3, the mass volume ratio of the natural polymer salt solution is 1-3%.

7. A composite hybrid carbon brush based on non-oxygen-producing photosynthetic bacteria, characterized in that: include: A fiber brush, a conductive high molecular polymer and a composite hybrid based on non-oxygen-producing photosynthetic bacteria as claimed in any one of claims 1 to 4; The composite hybrid based on non-oxygen-producing photosynthetic bacteria as described in any one of claims 1 to 4 is adhered and fixed to the bristle surface of the fiber brush through a conductive polymer hydrogel.

8. The method for preparing a composite hybrid carbon brush based on non-oxygen-producing photosynthetic bacteria according to claim 7, characterized in that: Includes steps: Step B1, soaking the conductive alginate-based polymer in a 100 mM excess CaCl2 solution for 1 day to obtain a rehydrated hydrogel; Step B2, adding a composite hybrid based on non-oxygen-producing photosynthetic bacteria as described in any one of claims 1 to 4 to the rehydrated hydrogel to obtain a conductive polymer / hybrid mixed suspension; Step B3: impregnate or spray the polymer / hybrid mixed suspension onto the bristle surface of the fiber brush, and solidify to obtain a composite hybrid carbon brush based on non-oxygen-producing photosynthetic bacteria.

9. Use of a composite hybrid based on non-oxygen-producing photosynthetic bacteria as described in any one of claims 1 to 4 or a composite hybrid carbon brush based on non-oxygen-producing photosynthetic bacteria as described in claim 7 in simultaneous carbon fixation and degradation of toxic and difficult-to-degrade organic pollutants.

10. The use according to claim 9, characterized in that: The application specifically includes: adding a composite hybrid based on non-oxygen-producing photosynthetic bacteria as described in any one of claims 1-2 or a composite hybrid carbon brush based on non-oxygen-producing photosynthetic bacteria as described in claim 7 to wastewater containing sulfadiazine, and simultaneously fixing carbon and degrading toxic and difficult-to-degrade organic pollutants under light.

Citation Information

Patent Citations

  • Rhodopseudomonas palustris-nano TiO2 composite material as well as preparation method and application thereof

    CN114956352A

  • Preparation method of chitosan modified polyurethane sponge carrier coupled S-type heterojunction photocatalyst and rhodopseudomonas palustris composite system

    CN115608417A

  • Method of reducing nitrate content in a plant

    US20160242362A1